Hierarchical pore ZSM-5 single crystal molecular sieve and preparation method and application thereof
The three-dimensional boundary method of synthesis of grade pore ZSM-5 single crystal molecular sieve and loading metal ions is solved, and the problems of low diffusion efficiency of ZSM-5 molecular sieve catalyst and complex metal load are achieved, achieving efficient phenol catalytic effect, which is convenient for large-scale application.
Patent Information
- Application Number
- CN202510618590.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-14
- Publication Date
- 2025-08-29
AI Technical Summary
The existing microporous structure of the ZSM-5 molecular sieve catalysts leads to low diffusion efficiency, carbon deactivation and metal loading complexity, which limits the catalytic efficiency and selectivity of phenol.
The grade pore ZSM-5 single crystal molecular sieve was synthesized by three-dimensional boundary method, and metal ions were loaded through the Si-OH structure platform to prepare metal @H-ZSM-5 catalysts, simplifying the process and improving catalytic performance.
It achieves high specific surface area and diffusion, improves catalytic efficiency after loading metals, and is simple to synthesis of catalysts, which is suitable for large-scale applications.
Smart Images

Figure CN120550852A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a hierarchical pore ZSM-5 single crystal molecular sieve and a preparation method and application thereof. Background Art
[0002] Phenol is a key organic chemical raw material in the petrochemical industry and a major derivative of propylene and benzene. It is primarily used in the production of chemical products and intermediates such as phenolic resin and bisphenol A. It also has important applications in the chemical raw materials, synthetic fibers, plastics, synthetic rubber, pharmaceuticals, and oil refining industries. Phenol can also be used as a solvent, reagent, and disinfectant, making the search for efficient phenol catalysts of great importance in both industry and scientific research.
[0003] The catalytic reaction of phenol is mainly divided into free radical reaction and non-free radical reaction. Free radical reaction refers to the decomposition of metal ions and H2O2 to obtain ·OH / ·OOH / ·O -2 Or bond with it to form peroxymetallic radicals (MOO·), followed by ·OH / ·OOH / ·O -2 Alternatively, peroxymetallic radicals attack benzene to produce phenol (e.g., Fenton / Fenton-like systems). Non-radical reactions involve metal-oxygen intermediates (e.g., M=O, MOM) as active species. Through electrophilic-nucleophilic pathways, the active intermediates attack benzene and then dehydrogenate to produce phenol. Both free radical and non-radical reactions require metal ion loading. However, current metal loading methods are complex and have low catalytic efficiency, limiting their large-scale application.
[0004] ZSM-5 molecular sieves are widely used in fields such as petroleum catalytic cracking and fine chemicals due to their high specific surface area, high hydrothermal stability, acid resistance, and excellent shape-selective catalytic performance. However, the ZSM-5 phenol catalysts currently used in industry contain only micropores, resulting in low diffusion efficiency and prone to carbon deposition and deactivation, leading to low catalyst efficiency.
[0005] At the same time, metals are difficult to load, which means that in the current research process of applying ZSM-5 molecular sieves to MTP catalytic reactions, the selectivity and catalytic efficiency of phenol are still low, which is one of the huge challenges currently facing the MTP reaction. Summary of the Invention
[0006] The present invention aims to synthesize hierarchical pore ZSM-5 single crystal molecular sieves rich in Si-OH structures through a three-dimensional confinement method. The hierarchical pore structure provides high specific surface area and diffusivity, and the opal morphology provides a rich Si-OH structural platform. A second purpose of the present invention is to load metal ions into the hierarchical pore ZSM-5 single crystal molecular sieve through the Si-OH rivet platform to synthesize a phenol catalyst (metal@H-ZSM-5) with excellent catalytic performance. The process is simple, reproducible, and convenient for large-scale industrial applications.
[0007] In order to achieve the above purpose, the technical solutions adopted are as follows: A method for preparing a hierarchical pore ZSM-5 single crystal molecular sieve comprises the following steps: (1) Polystyrene microspheres, silica beads, sucrose and sulfuric acid are uniformly mixed, and the mixture is deposited and dried in an oven to obtain a polystyrene microsphere / silica beads / carbon precursor material; (2) calcining the precursor material under a nitrogen atmosphere, then adding it to a hydrofluoric acid aqueous solution and stirring to obtain a suspension, filtering it, and drying it to obtain a carbon template material with a hierarchical structure; (3) adding a mixed solution of deionized water, tetrapropylammonium hydroxide, aluminum isopropoxide, and tetraethyl orthosilicate to the carbon template material, mixing, and drying to obtain a mixture; (4) The mixture is subjected to steam-assisted crystallization, filtration, drying, and calcination to obtain a hierarchical pore ZSM-5 single crystal molecular sieve.
[0008] According to the above scheme, in step 1, the mass ratio of polystyrene microspheres, silica beads, sucrose and sulfuric acid is 100:(10-20):(10-20):(1-2).
[0009] According to the above scheme, the sizes of the polystyrene microspheres and silica in step 1 are both 400-600 nm.
[0010] According to the above scheme, the calcination temperature in step 2 is 600-700°C and the calcination time is 5-6 h.
[0011] According to the above scheme, in step 2, the hydrofluoric acid and deionized water in the hydrofluoric acid aqueous solution are mixed in a volume ratio of 3:2.
[0012] According to the above scheme, the drying temperature in step 2 is 70-90°C and the drying time is 24-48 h.
[0013] According to the above scheme, the molar ratio of deionized water, tetrapropylammonium hydroxide, aluminum isopropoxide, and tetraethyl orthosilicate in step 3 is 18:(0.17-0.19):(0.018-0.022):(0.9-1.1).
[0014] According to the above scheme, the mixed solution in step 3 is mixed with the carbon template material at a liquid-to-solid ratio of 8-12 mL / g.
[0015] According to the above scheme, the calcination temperature in step 4 is 550-600°C and the calcination time is 6-8h.
[0016] A method for preparing a metal@ZSM-5 catalyst comprises the following steps: (a) adding the hierarchical pore ZSM-5 single crystal molecular sieve molecules to an ammonium nitrate solution, heating and stirring, filtering, drying, and calcining to obtain an H-type ZSM-5 molecular sieve; (b) adding the H-type ZSM-5 molecular sieve to a metal nitrate solution, heating and stirring, filtering, drying, and calcining to obtain a metal@ZSM-5 catalyst.
[0017] According to the above scheme, in step (a), the solid-liquid ratio of the hierarchical pore ZSM-5 single crystal molecular sieve molecules to the ammonium nitrate solution is 0.1-0.2 g / mL; the concentration of the ammonium nitrate solution is 0.08-0.1 g / mL, the calcination temperature is 550-600°C, and the calcination time is 6-8 hours.
[0018] According to the above scheme, in step (b), the solid-liquid ratio of H-type ZSM-5 molecular sieve to metal nitrate solution is 0.1-0.2 g / mL; the metal nitrate solution is 0.08-0.1 g / mL, the calcination temperature is 500-550°C, and the calcination time is 3-5h.
[0019] According to the above scheme, the metal nitrate in step (b) is copper nitrate.
[0020] Compared with the prior art, the present invention has the following beneficial effects: The present invention adopts a three-dimensional confinement method to synthesize a molecular sieve with a hierarchical pore structure. The hierarchical pore structure provides a high specific surface area and diffusivity. The opal morphology provides a rich Si-OH structural platform and rivets metal therein. The preparation method is simple and the catalytic effect is better.
[0021] The present invention synthesizes hierarchical pore ZSM-5 molecular sieves through a three-dimensional confinement method, loads metal nanoparticles onto the hierarchical pore ZSM-5 single crystal molecular sieve through an amine exchange plus ion exchange method, forms metal ion active sites in the catalyst to obtain a metal@ZSM-5 catalyst, achieves excellent catalytic efficiency, is simple to synthesize, is green and pollution-free, and is easy to promote and apply on a large scale.
[0022] This invention uses a three-dimensional confinement method to enrich the ZSM-5 molecular sieve single crystal with a rich Si-OH structure, providing a large number of active sites and allowing metals to be riveted into them. Furthermore, different metals can be loaded according to different reactions, achieving catalytic regulation of multiple reactions and synthesizing molecular sieve catalysts with excellent catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 : SEM images of the products obtained in Example 1 and Example 2.
[0024] Figure 2 : XRD patterns of Cu@ZSM-5 molecular sieve catalysts with different concentrations obtained in Example 2.
[0025] Figure 3 : Pore size distribution diagram of Cu@ZSM-5 molecular sieve catalysts with different concentrations obtained in Example 2.
[0026] Figure 4 : Characterization diagram of the synthesis of phenol by the catalytic reaction of benzene using the molecular sieve catalyst obtained in the examples and comparative examples.
[0027] Figure 5 : Infrared spectra of the molecular sieves obtained in the examples and comparative examples and after loading metallic copper. DETAILED DESCRIPTION
[0028] The following examples further illustrate the technical solutions of the present invention but are not intended to limit the scope of protection of the present invention.
[0029] The specific embodiment provides a hierarchical pore ZSM-5 single crystal molecular sieve: (1) Polystyrene microspheres are obtained by emulsion polymerization of styrene. Commercial polystyrene microspheres can also be purchased directly.
[0030] (2) The polystyrene microspheres obtained in step (1) are uniformly mixed with silica beads, sucrose and sulfuric acid solution, and then transferred into an oven for deposition and drying to obtain a polystyrene microsphere / silica beads / carbon mixed precursor material; wherein the mass ratio of polystyrene microspheres, silica beads, sucrose and sulfuric acid is 100:(10-20):(10-20):(1-2).
[0031] (3) The precursor material obtained in step (2) was calcined and then added to a mixed solution of deionized water and hydrofluoric acid, and stirred to obtain a suspension; the ratio of deionized water to hydrofluoric acid was 150 mL:100 mL, and the mixture was stirred for 6 h at a stirring rate of 500 r / min.
[0032] (4) The suspension obtained in step (3) is filtered and dried to obtain a carbon template material with a hierarchical structure; the drying temperature is 80°C and the drying time is 24 to 48 hours.
[0033] (5) Deionized water, tetrapropylammonium hydroxide, aluminum isopropoxide, and tetraethyl orthosilicate are mixed and stirred, and then added to the carbon template material obtained in step (4), and dried to obtain a mixture; wherein the amounts of deionized water, tetrapropylammonium hydroxide, aluminum isopropoxide, and tetraethyl orthosilicate are 18:(0.17-0.19):(0.018-0.022):(0.9-1.1), respectively.
[0034] (6) The mixture obtained in step (5) is subjected to steam-assisted crystallization, filtration, drying, and calcination to obtain a graded pore ZSM-5 single crystal molecular sieve; the calcination temperature is 550° C., and the calcination time is 7 h.
[0035] The specific embodiment also provides a metal @ ZSM-5 catalyst: (1) The obtained hierarchical pore ZSM-5 single crystal molecular sieve was added to an ammonium nitrate solution, heated and stirred, filtered, dried, and calcined to obtain the desired H-type ZSM-5 catalyst sample; the amounts of the molecular sieve, NH4NO3, and deionized water used were 0.5 g, 0.4 g, and 5 mL, respectively. The heating temperature was 80°C for 2 h; the drying temperature was 100°C for 6 h; and the calcination temperature was 550°C for 7 h.
[0036] (2) Add the obtained molecular sieve to a nitric acid metal solution, heat and stir, filter, dry, repeat once, and calcine to obtain the desired metal@H-ZSM-5; wherein the heating and stirring conditions are stirring at 600 r / min at 50°C for 12 hours, drying at 80°C for 12 hours, and calcining at 500°C for 4 hours. Example 1 A method for preparing an H-ZSM-5 catalyst with an ordered interconnected structure comprises the following steps: (1) 47 g of styrene, 360 mL of deionized water, and 0.15 g of sodium dodecyl sulfate were added to a three-necked flask, stirred at room temperature for 30 min, heated to 75 °C and stabilized for 30 min, and then 0.2 g of potassium persulfate was added and stirred for 7 h at a stirring rate of 600 r / min to obtain polystyrene microspheres; (2) The polystyrene microspheres obtained in step (1) were uniformly mixed with silica beads, sucrose and sulfuric acid solution in a mass ratio of 100:15:15:1.5. The specific operation was as follows: the polystyrene emulsion was first stirred for 1 hour, and then the silica beads and sucrose were added and stirred for 1 hour. Finally, 10 wt% sulfuric acid solution was added and stirred for 1 hour. Then, gradient drying was performed in an oven (60°C for 12 hours, 110°C for 6 hours, and 160°C for 6 hours) to obtain a polystyrene microsphere / silica beads / carbon mixed precursor material; (3) The precursor material obtained in step (2) was calcined in an inert gas atmosphere from room temperature to 300°C, kept warm for 1 hour, then to 400°C, kept warm for 1 hour, then to 500°C, kept warm for 1 hour, then to 650°C, kept warm for 5 hours, with a heating rate of 1°C / min. It was then added to a mixed solution of deionized water and hydrofluoric acid in a ratio of 150 mL:100 mL, and stirred at 500 r / min for 6 hours to obtain a suspension; (4) The suspension obtained in step (3) was filtered and dried at 80° C. for 24 to 48 hours to obtain a carbon template material with a hierarchical structure; (5) Deionized water, tetrapropylammonium hydroxide, aluminum isopropoxide, and tetraethyl orthosilicate were mixed and stirred. Deionized water, tetrapropylammonium hydroxide, and aluminum isopropoxide were first mixed and stirred for 1 hour, and then tetraethyl orthosilicate was added dropwise and stirred for 3 hours at a stirring rate of 500 r / min. Then, the mixture was added to the carbon template material obtained in step (4). The ratio of the solution to the carbon template material was 2 mL: 0.2 g. The mixture was aged at 60°C for 16 hours to obtain a mixture. (6) The mixture obtained in step (5) was subjected to steam-assisted crystallization at 180°C for 8 h, cooled, filtered, dried at 80°C for 2 h, and calcined at 550°C for 7 h at a heating rate of 2°C / min using graded pore H-ZSM-5 molecular sieve.
[0037] Figures 1a and 1b are SEM images of the hierarchical pore ZSM-5 molecular sieve (H-ZSM-5) obtained in this example. The images demonstrate that the H-ZSM-5 prepared by steam-assisted crystallization possesses a continuous, hierarchical pore structure.
[0038] Example 2 A method for preparing hierarchical pore ZSM-5 single crystal molecular sieve loaded with metallic Cu (Cu@H-ZSM-5) by ion exchange. The preparation method is as follows: (1) The hierarchical pore ZSM-5 single crystal molecular sieve obtained in Example 1 was added to an ammonium nitrate solution, heated and stirred, filtered, dried, and calcined to obtain the desired H-type ZSM-5 catalyst sample; the amounts of the molecular sieve, NH4NO3, and deionized water used were 0.5 g, 0.4 g, and 5 mL, respectively. The heating temperature was 80°C for 2 hours, the drying temperature was 100°C for 6 hours, and the calcination temperature was 550°C for 7 hours.
[0039] (2) The obtained molecular sieve was added to a Cu(NO3)2 solution, heated and stirred, filtered, dried, repeated once, and calcined to obtain a ZSM-5 molecular sieve catalyst loaded with metal Cu (Cu@H-ZSM-5); wherein the heating and stirring conditions were stirring at 600 r / min at 50°C for 12 h, drying at 80°C for 12 h, and calcining at 500°C for 4 h.
[0040] Figures 1c and 1d show SEM images of the Cu-loaded ZSM-5 zeolite catalyst (Cu@H-ZSM-5) obtained in this example. These images demonstrate that the Cu-loaded zeolite single crystals are composed of nanospheres, indicating the presence of two additional pores within the face-centered cubic (FCC) stacking structure: octahedral pores (macroporations) and tetrahedral pores (mesoporations). The synthesized sample exhibits a regular three-dimensional structure, excellent crystallinity, and uniform growth.
[0041] Figure 2 shows the XRD patterns of the Cu-loaded ZSM-5 molecular sieve catalyst (Cu@H-ZSM-5) obtained in this example. The XRD peak curves are for Z5 (1 M), Z5 (0.5 M), Z5 (0.25 M), Z5 (0.1 M), and Z5, respectively. It is clearly observed that the MFI structure and crystallinity of the samples remain unchanged after Cu loading.
[0042] Figure 3 shows the pore size distribution of the Cu-loaded ZSM-5 molecular sieve catalyst (Cu@H-ZSM-5) obtained in this example. The pore size distribution curves are for Z5 (1 M), Z5 (0.5 M), Z5 (0.25 M), Z5 (0.1 M), and Z5. The figure shows a slight decrease in the catalyst's specific surface area and pore volume after the introduction of Cu, which is attributed to the incorporation of Cu species into the molecular sieve's micropores.
[0043] Figure 4 shows the conversion rate of benzene and the selectivity for phenol during the benzene catalytic reaction of the ZSM-5 molecular sieve catalyst loaded with metal Cu (Cu@H-ZSM-5) obtained in this example. The image shows that compared with the unloaded sample, the conversion rate of benzene and the selectivity for phenol are greatly improved after loading Cu, among which H-ZSM-5 (0.5 M) has the best catalytic effect.
[0044] Figure 5 This is an infrared spectrum of the Cu-loaded ZSM-5 molecular sieve catalyst obtained in this example. The image shows that compared to the traditional ZSM-5 molecular sieve (C-ZSM-5), the hierarchical pore ZSM-5 molecular sieve (H-ZSM-5) contains more Si-OH structures. However, the presence of Si-OH structures decreases after Cu loading. This is because the Si-OH structures combine with Cu to form Si-O-Cu structures.
[0045] Comparative Example 1 Repeat Example 2, omitting step 1, and directly adding the hierarchical pore ZSM-5 single crystal molecular sieve obtained in Example 1 into the Cu(NO3)2 solution, while keeping the other process conditions unchanged.
[0046] The conversion rate of benzene and the selectivity of phenol in the benzene catalytic reaction of the ZSM-5 molecular sieve catalyst loaded with metal Cu obtained in this comparative example 1 are shown in the attached figure. Figure 4 As can be seen from the attached figure, when the same nitric acid metal solution (0.5 M) is added, the conversion rate and selectivity of phenol for the catalyst obtained by the ion exchange method without amine exchange are greatly reduced.
[0047] The specific embodiment also provides a method for preparing a conventional ZSM-5 molecular sieve: (1) Deionized water, tetrapropylammonium hydroxide (25%), sodium hydroxide, sodium aluminate, and tetraethyl orthosilicate were mixed and stirred in a mass ratio of 16.28 g: 1.627 g: 0.184 g: 0.0109 g: 4.1666 g. Deionized water, tetrapropylammonium hydroxide, sodium hydroxide, and sodium aluminate were first mixed and stirred until clear, and then tetraethyl orthosilicate was added dropwise and stirred for 4 h at a stirring rate of 600 r / min to obtain a molecular sieve precursor solution. (2) The precursor solution obtained in step (1) was transferred to a 180°C oven for hydrothermal crystallization for 48 hours, cooled, filtered, dried at 80°C for 2 hours, and calcined at 550°C for 7 hours at 2°C / min to obtain Na-type C-ZSM-5 molecular sieve; (3) The Na-type C-ZSM-5 molecular sieve obtained in step (2) was subjected to ammonium exchange treatment, and 1M ammonium nitrate solution and Na-type C-ZSM-5 molecular sieve were mixed in a ratio of 10mL:1g, stirred at 80°C for 6h, filtered, dried at 80°C for 2h, and calcined at 550°C for 7h at a heating rate of 2°C / min to obtain H-type C-ZSM-5 molecular sieve.
[0048] Comparative Example 2 Example 2 was repeated, except that the hierarchical pore ZSM-5 single crystal molecular sieve obtained in Example 1 was replaced by the H-type C-ZSM-5 molecular sieve obtained in Comparative Example 1, and the other conditions remained unchanged.
[0049] The conversion rate of benzene and the selectivity of phenol in the benzene catalytic reaction of the ZSM-5 molecular sieve catalyst (Cu / C-ZSM-5) obtained in this comparative example are shown in the attached figure. Figure 4 From the figure, it can be seen that under the condition of the same metal loading (0.5M), the single crystal yield and selectivity of hierarchical pore ZSM-5 molecular sieve are greatly improved compared with the traditional C-ZSM-5 molecular sieve.
[0050] Figure 5 This is a characterization diagram obtained by infrared testing of the traditional ZSM-5 molecular sieve catalyst (Cu@C-ZSM-5) loaded with metal Cu obtained in this comparative example. It can be found that compared with the hierarchical pore ZSM-5 molecular sieve single crystal (Cu@H-ZSM-5), the traditional ZSM-5 molecular sieve (Cu@C-ZSM-5) contains fewer Si-0H structures.
Claims
1. A method for preparing hierarchical pore ZSM-5 single crystal molecular sieve, characterized in that The following steps are involved: (1) Polystyrene microspheres, silica beads, sucrose and sulfuric acid are uniformly mixed, and the mixture is deposited and dried in an oven to obtain a polystyrene microsphere / silica beads / carbon precursor material; (2) calcining the precursor material under a nitrogen atmosphere, then adding it to a hydrofluoric acid aqueous solution and stirring to obtain a suspension, filtering it, and drying it to obtain a carbon template material with a hierarchical structure; (3) adding a mixed solution of deionized water, tetrapropylammonium hydroxide, aluminum isopropoxide, and tetraethyl orthosilicate to the carbon template material, mixing, and drying to obtain a mixture; (4) The mixture is subjected to steam-assisted crystallization, filtration, drying, and calcination to obtain a hierarchical pore ZSM-5 single crystal molecular sieve.
2. The method for preparing the hierarchical pore ZSM-5 single crystal molecular sieve according to claim 1, characterized in that In step 1, the mass ratio of polystyrene microspheres, silica beads, sucrose and sulfuric acid is 100:(10-20):(10-20):(1-2); the sizes of the polystyrene microspheres and silica beads are both 400-600 nm.
3. The method for preparing the hierarchical pore ZSM-5 single crystal molecular sieve according to claim 1, characterized in that In step 2, the calcination temperature is 600-700° C., and the calcination time is 5-6 h. The hydrofluoric acid aqueous solution contains hydrofluoric acid and deionized water in a volume ratio of 3:
2. The drying temperature is 70-90° C., and the drying time is 24-48 h.
4. The method for preparing the hierarchical pore ZSM-5 single crystal molecular sieve according to claim 1, characterized in that In step 3, the molar ratio of deionized water, tetrapropylammonium hydroxide, aluminum isopropoxide, and tetraethyl orthosilicate is 18:(0.17-0.19):(0.018-0.022):(0.9-1.1); the mixed solution is mixed with the carbon template material at a liquid-to-solid ratio of 8-12 mL / g.
5. The method for preparing the hierarchical pore ZSM-5 single crystal molecular sieve according to claim 1, characterized in that In step 4, the calcination temperature is 550-600° C., and the calcination time is 6-8 hours.
6. A hierarchical pore ZSM-5 single crystal molecular sieve, characterized in that The crystalline ZSM-5 molecular sieve is prepared by the method for preparing the hierarchical pore ZSM-5 single crystal molecular sieve according to claim 1.
7. A method for preparing a metal@ZSM-5 catalyst, characterized in that The following steps are involved: (a) adding the hierarchical pore ZSM-5 single crystal molecular sieve molecules according to claim 6 to an ammonium nitrate solution, heating and stirring, filtering, drying, and calcining to obtain an H-type ZSM-5 molecular sieve; (b) adding the H-type ZSM-5 molecular sieve to a metal nitrate solution, heating and stirring, filtering, drying, and calcining to obtain a metal@ZSM-5 catalyst.
8. The method for preparing the metal@ZSM-5 catalyst according to claim 7, characterized in that In step (a), the solid-liquid ratio of the hierarchical pore ZSM-5 single crystal molecular sieve molecules to the ammonium nitrate solution is 0.1-0.2 g / mL; the concentration of the ammonium nitrate solution is 0.08-0.1 g / mL, the calcination temperature is 550-600° C., and the calcination time is 6-8 hours.
9. The method for preparing the metal@ZSM-5 catalyst according to claim 7, characterized in that In step (b), the solid-liquid ratio of the H-type ZSM-5 molecular sieve to the metal nitrate solution is 0.1-0.2 g / mL; the metal nitrate solution is 0.08-0.1 g / mL, the calcination temperature is 500-550° C., and the calcination time is 3-5 hours.
10. The method for preparing the metal@ZSM-5 catalyst according to claim 7, characterized in that In step (b), the metal nitrate is copper nitrate.